The relationship between fibromyalgia syndrome and inflammation parameters in hemodialysis patients - Karahisar Şirali, Semahat; Büberci, Refika (The European Research Journal, 2024)
Objectives: Diagnosing fibromyalgia, a condition characterized by widespread body pain of unknown origin accompanied by various additional symptoms, poses a challenge in hemodialysis patients, who frequently experience musculoskeletal disorders. To investigate the relationship between fibromyalgia syndrome and inflammation parameters in hemodialysis patients. Methods: The study enrolled 311 hemodialysis patients undergoing treatment for over three months. Demographic characteristics, complete blood count, and biochemical values were documented as part of the study. To assess fibromyalgia, the researchers recorded the patients scores on the Generalized Pain Scale and Symptom Severity Scale based on data provided by the American College of Rheumatology. The patients were then divided into two groups: those with fibromyalgia and those without fibromyalgia, and their laboratory values and rates were compared. Inflammatory parameters such as erythrocyte sedimentation rate, c reactive protein, monocyte-to-lymphocyte ratio, lymphocyte-to-c reactive protein ratio, and c reactive protein to albumin ratio were recorded. Results: The study included 311 patients on hemodialysis for more than three months. Among the study participants, 48.9% of the patients and 62.9% of those with fibromyalgia were women. The mean age was 54±26 years and was significantly higher in patients with fibromyalgia (P